Severity of leukoaraiosis, leptomeningeal collaterals, and clinical outcomes after intra-arterial therapy in patients with acute ischemic stroke. (10th April 2014) - Giurgiutiu, Dan-Victor; Yoo, Albert J; Fitzpatrick, Kaitlin; Chaudhry, Zeshan; Leslie-Mazwi, Thabele; Schwamm, Lee H; Rost, Natalia S
Abstract : Background and purpose: Leukoaraiosis (LA) is defined as ischemic white matter lesions associated with increased stroke risk and poor post-stroke outcomes. These lesions are likely the result of diffuse angiopathic changes affecting the cerebral small vessels. We investigated whether pre-existing LA burden is associated with outcomes in patients with large cerebral artery occlusion undergoing intra-arterial therapy (IAT) for acute ischemic stroke (AIS). Methods: We analyzed consecutive AIS subjects undergoing IAT from the institutional Get With The Guidelines-Stroke database enrolled between January 1, 2007 and June 30, 2009, who had National Institutes of Health Stroke Scale scores of ≥8, baseline diffusion weighted imaging volume ≤100 mL, and evidence of proximal artery occlusion (PAO) on pre-IAT computed tomography angiography (CTA). LA volume (LAv) was assessed on fluid attenuated inversion recovery MRI using a validated semi-automated protocol. We used CTA for collateral grade, post-IAT angiogram for recanalization status (Thrombolysis in Cerebral Infarction score ≥2b), and the 24 h head CT for symptomatic intracranial hemorrhage. Logistic regression was used to determine independent predictors of 90 day post-stroke good functional outcome (modified Rankin Scale score ≤2) and mortality. Results: Increasing LAv independently reduced the odds of good collateral grade (OR 0.85, 95% CI 0.73 to 0.98). Good functional outcome was independently predicted by intravenous tissue plasminogen activator use (OR 12.86, 95% CI 2.20 to 76.28), and recanalization status (OR 6.94, 95% CI 1.56 to 30.86). Mortality was independently associated with recanalization status (OR 0.08, 95% CI 0.01 to 0.51), age (OR 1.08, 95% CI 1.01 to 1.15), and antecedent use of hypoglycemic agents (OR 6.55, 95% CI 1.58 to 54.01). Conclusions: Severity of LA is linked to poor collateral grade in AIS patients undergoing IAT for PAO; however, greater LAv appears not to be a contraindication for acute intervention.